Stress and pain neuroendocrine regulation in bullfighting (Bos Taurus L.): preliminary study - Illera, Juan Carlos; Gil, Fernando; Silván, Gema (Revista Complutense de Ciencias Veterinarias, 2007)
Sin resumen